2019
DOI: 10.1111/epi.16322
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management for adults with epilepsy: Aggregate Managing Epilepsy Well Network findings on depressive symptoms

Abstract: Objective To assess depressive symptom outcomes in a pooled sample of epilepsy self‐management randomized controlled trials (RCTs) from the Managing Epilepsy Well (MEW) Network integrated research database (MEW DB). Methods Five prospective RCTs involving 453 adults with epilepsy compared self‐management intervention (n = 232) versus treatment as usual or wait‐list control outcomes (n = 221). Depression was assessed with the nine‐item Patient Health Questionnaire. Other variables included age, gender, race, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…From the electronic search, 698 articles were identified, and after careful reading, 42 studies were found to meet the preliminary criteria. We further excluded 34 articles based on study design, improper inclusion criteria, or insufficient data to abstract, leaving eight studies (19)(20)(21)(22)(23)(24)(25)(26) meeting the inclusion criteria and included in the metaanalysis (Figure 1).…”
Section: Search Processmentioning
confidence: 99%
“…From the electronic search, 698 articles were identified, and after careful reading, 42 studies were found to meet the preliminary criteria. We further excluded 34 articles based on study design, improper inclusion criteria, or insufficient data to abstract, leaving eight studies (19)(20)(21)(22)(23)(24)(25)(26) meeting the inclusion criteria and included in the metaanalysis (Figure 1).…”
Section: Search Processmentioning
confidence: 99%
“…Another RCT compared the effectiveness of a multicomponent SM intervention consisting of five weekly, 2-hour group sessions each followed by a 2-hour group session after three weeks with usual care; they found no difference in measures of self-efficacy, though did find improvements in some epilepsy QOL domains and decreases in measures of ASM side effects [13]. Other studies examining the efficacy of in-person, group-based, online or phone/internet SM interventions, including the Centers for Disease Control and Prevention-supported Managing Epilepsy Well (MEW) network programs, did show improvement in epilepsy SM and QOL [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Engaging with new technologies could potentially add to inequalities and health disparities and this should be avoided by recognizing specific populations and groups who might be at higher risk of digital exclusion [5,9,12] or at risk of providing sub-optimal data. Evidence has indicated that patient-related factors, such as age [1,9,12] can influence interaction with new technologies (also in terms of technical support needed 12]), while other studies suggested that individuals with less education [19] and people with psychiatric comorbidities may be generally subject to poor outcomes [19][20][21][22]. In our population, technology self-management did not differ between younger and older participants, and no differences were found according to the level of education or to the presence of psychiatric comorbidities, suggesting that a tailored training could, at least in part, level the disparities that might otherwise occur.…”
Section: Discussionmentioning
confidence: 99%